2020
DOI: 10.1097/md.0000000000021572
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic vertebral fractures involve the anterior end plate more than the posterior end plate

Abstract: Traumatic end plate fractures (EPFs) refers to the EPF caused by trauma, rather than the pathological status of the end plate (EP). However, some old traumatic EPFs may be mistaken as osteoporotic in the elderly. The objective of this study is to describe the radiological features of traumatic EPF in different traumatic fracture type patients presenting in the Emergency department setting. And to compare the result with osteoporotic vertebral fracture (VF). This study retrospectively analyzed the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In the biomechanical performance of FSUs, motion stiffness of flexion, extension and lateral bending was used instead of direct pullout test from construct rod. Studies retrospectively analyzed the anatomical location of acute thoracolumbar vertebral fractures and found that the fracture rate of the superior endplate is much higher than that of the inferior endplate (Che-Nordin et al, 2018;Wang et al, 2020). Our biomechanical results suggested that MT screws are not only superior in pullout strength but also potentially decrease future upper instrumented fractures.…”
Section: Figurementioning
confidence: 63%
“…In the biomechanical performance of FSUs, motion stiffness of flexion, extension and lateral bending was used instead of direct pullout test from construct rod. Studies retrospectively analyzed the anatomical location of acute thoracolumbar vertebral fractures and found that the fracture rate of the superior endplate is much higher than that of the inferior endplate (Che-Nordin et al, 2018;Wang et al, 2020). Our biomechanical results suggested that MT screws are not only superior in pullout strength but also potentially decrease future upper instrumented fractures.…”
Section: Figurementioning
confidence: 63%